(untitled) (Security Dialogues, 2024)
Until 2022, European citizens had not faced any direct physical threat to their Critical Energy Infrastructure (CEI) for generations. However, in September of that year, everything changed with the sabotage of the Nord Stream 1 and 2 pipelines, which connected Germany to Russia. The research begins from this period due to the significance of both the year and the event. That year saw the outbreak of the conflict in Ukraine, introducing a new (in)security landscape for Europe. The event was also unprecedented, emphasizing the importance of this starting point. This shifted CEI protection to a top priority for both the EU and NATO, prompting action from both international organizations to prevent similar incidents in the future. However, the October 2023 Balticconnector incident — damage to an underwater gas pipeline and communication cable between Finland and Estonia — revealed inefficiencies in the synergy between NATO and the EU regarding CEI protection. This raised the research question: is there any overlap between the two organizations in CEI protection, and if so, in which areas? Through an in-depth case study using the analytical tool of organizational overlap, it was found that there is significant overlap between the EU and NATO in their efforts to protect European CEI, particularly in the areas of division of labor and mandate. The study examined their strategies, discourse, methods, and intentions, concluding that coordination remains insufficient. Although steps have been taken to address the issue—such as the creation of the EU-NATO Task Force on CEI resilience and the “Coherent Resilience 2023 Baltic” tabletop exercise—progress in 2024 remains limited, leaving much to be desired from both organizations in this field.